Establishment and preliminary outcomes of a palliative care research network. Issue 1 (19th June 2015) - Hudson, Peter; Street, Annette; Graham, Suzanne; Aranda, Sanchia; O'Connor, Margaret; Thomas, Kristina; Jackson, Kate; Spruyt, Odette; Ugalde, Anna; Philip, Jennifer
ABSTRACT: Objective: The difficulties in conducting palliative care research have been widely acknowledged. In order to generate the evidence needed to underpin palliative care provision, collaborative research is considered essential. Prior to formalizing the development of a research network for the state of Victoria, Australia, a preliminary study was undertaken to ascertain interest and recommendations for the design of such a collaboration. Method: Three data-collection strategies were used: a cross-sectional questionnaire, interviews, and workshops. The questionnaire was completed by multidisciplinary palliative care specialists from across the state ( n = 61); interviews were conducted with senior clinicians and academics ( n = 21) followed by two stakeholder workshops ( n = 29). The questionnaire was constructed specifically for this study, measuring involvement of and perceptions of palliative care research. Results: Both the interview and the questionnaire data demonstrated strong support for a palliative care research network and aided in establishing a research agenda. The stakeholder workshops assisted with strategies for the formation of the Palliative Care Research Network Victoria (PCRNV) and guided the development of the mission and strategic plan. Significance of results: The research and efforts to date to establish the PCRNV are encouraging and provide optimism for the evolution of palliative care research in Australia. The international implications are highlighted.